2016
DOI: 10.1111/boj.12439
|View full text |Cite
|
Sign up to set email alerts
|

Leaf anatomy inAllagoptera(Arecaceae)

Abstract: The small genus Allagoptera (Arecaceae) includes six South American species. Their leaves have several anatomical characters that remain unexplored. We provide a detailed description of the leaf anatomy of Allagoptera, using 128 characters, and an identification key. Given the gradual size variation in the mesophyll cells in some species, a new classification of 'gradual dorsiventral mesophyll' is proposed here. We report for the first time 'subsidiary ledges' in the stomatal complex of Arecaceae. We propose u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
17

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 31 publications
(46 reference statements)
0
9
0
17
Order By: Relevance
“…According to Glassman (), leaf anatomy is of limited use for the classification of Attalea , although it seems promising in the closely allied genus Syagrus , in which variation was found to be congruent with molecular data (Noblick, ) and in the six Allagoptera spp. that have clearly distinct leaf anatomies (Pinedo et al ., ; this issue).…”
Section: Introductionmentioning
confidence: 94%
“…According to Glassman (), leaf anatomy is of limited use for the classification of Attalea , although it seems promising in the closely allied genus Syagrus , in which variation was found to be congruent with molecular data (Noblick, ) and in the six Allagoptera spp. that have clearly distinct leaf anatomies (Pinedo et al ., ; this issue).…”
Section: Introductionmentioning
confidence: 94%
“…Even though it has been useful in distinguishing species from other genera, such as Allagoptera ( Pinedo et al 2016 ), Oenocarpus ( Silva and Potiguara 2008 ; Tomlinson et al 2011 ) and Syagrus ( Noblick 2013 ), the leaf margin format showed intraspecific variation in part of the Butia species analysed here, reason that justified the exclusion of this character in the proposed key. Even when not variable within the same species, data such as epicuticular wax ( Barthlott 1981 ) require more refined and costly methodologies.…”
Section: Discussionmentioning
confidence: 82%
“…Because of this, taxonomy of Arecaceae traditionally has also been based on anatomical aspects of the organs, mainly of the leaf blade ( Tomnlinson 1961 ; Tomnlinson et al 2011 ; Noblick 2013 , 2014 ; Martins et al 2015 ; Sant’Anna-Santos et al 2015 ; Pinedo et al 2016 ; Vianna et al 2017 ). The leaf blade has provided useful characters to discriminate between species in some genera of the family, such as Oenocarpus ( Silva and Potiguara 2008 ; Tomnlinson et al 2011 ), Syagrus ( Glassman 1970 ; Tomnlinson et al 2011 ; Noblick 2013 ; Noblick et al 2014 ), Allagoptera ( Tomnlinson et al 2011 ; Martins et al 2015 ; Pinedo et al 2016 ), Parajubaea ( Meerow et al 2009 ; Tomnlinson et al 2011 ), Acrocomia ( Vianna et al 2017 ) and even Butia ( Noblick 2014 ; Sant’Anna-Santos et al 2015 ). A detailed comparative study of the leaf anatomy of Butia provided useful characters that corroborated the split of B. odorata from B. capitata and aid in their distinction ( Sant’Anna-Santos et al 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the porous restinga soils result in low soil fertility and low water retention capacity (Cooper et al 2017), which may impose constraints on plant biomass productivity (Lambers et al 2008, Santiago-garcía et al 2019. In water limited conditions, plants exhibit more conservative strategies, such as small body size and low specific leaf area (Cornwell andAckerly 2009, Katabuchi et al 2012), and the production of thick and scleromorphic leaves with increased longevity (Wright et al 2004, Lambers et al 2008, as are typically found in restinga plant species (Mantuano et al 2006, De Aguiar-Dias et al 2012, Melo Júnior and Torres Boeger 2015, Pinedo et al 2016.…”
Section: )mentioning
confidence: 99%